Effects of licorice root extract on the number of nocturnal hot flashes in menopausal women - Nahidi, F; Zare, E; Mojab, F; Alavi Majd, H (Advances in Nursing & Midwifery, 2010)
Background and aim Menopause entails many complications on women’s quality of life. Hot flashes is the most common and bothersome effect, mainly treated with hormonal therapy. However, because of its side effects, there is controversy over its administration. Thus, therapies with fewer complications such as herbs warrant investigation. The aim of this randomized double-blind clinical trial was to determine the effects of licorice root extract on the number of nocturnal hot flashes in menopausal women referring to healthcare centers affiliated to Shahid Beheshti University of Medical Sciences in 2008. Materials and methods 68 women were selected with purposive sampling method and randomly divided into 2 equal experimental and placebo groups. After taking their consent, data were gathered with a questionnaire and information forms validated through content method. Reliability was ensured by using standard brands for meter band, weights, stethoscope and sphygmomanometer calibrated according to guidelines of manufacturers. Both experimental and placebo groups took capsules containing 330 mg licorice and starch 3 times a day (morning, noon and night) over 4 weeks respectively. The numbers of nocturnal hot flashes were measured from 2 weeks before the intervention to the end of it. Data were analyzed by SPSS 11.5. Findings Means of age, duration of amenorrhea and duration of hot flashes were 53.13, 1.65 and 1.65 respectively. The numbers of hot flashes in the experimental group were 4.82 before the intervention and 1.05 after it with a significant difference. However, no significant difference was found before and after the intervention in the placebo group. Conclusion Licorice as an herb may decrease the number of nocturnal hot flashes in menopausal women, increasing their physical and psychological health. Keywords: Hot flashes, Menopause, Licorice. *Corresponding Author: Fatemeh Nahidi. Lecturer, Dept. of Midwifery, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Tehran, Iran. E-mail: nahidifateme@yahoo.com